Glia from the central and peripheral nervous system are differentially affected by paclitaxel chemotherapy via modulating their neuroinflammatory and neuroregenerative properties - Klein, Ines; Boenert, Janne; Lange, Felix; Christensen, Britt; Wassermann, Meike K.; Wiesen, Martin H. J.; Olschewski, Daniel Navin; Rabenstein, Monika; Müller, Carsten; Lehmann, Helmar C.; Fink, Gereon Rudolf; Schroeter, Michael; et al. (Frontiers in Pharmacology, 2022)
Glia are critical players in defining synaptic contacts and maintaining neuronal homeostasis. Both astrocytes as glia of the central nervous system (CNS), as well as satellite glial cells (SGC) as glia of the peripheral nervous system (PNS), intimately interact with microglia, especially under pathological conditions when glia regulate degenerative as well as regenerative processes. The chemotherapeutic agent paclitaxel evokes peripheral neuropathy and cognitive deficits; however, the mechanisms underlying these diverse clinical side effects are unclear. We aimed to elucidate the direct effects of paclitaxel on the function of astrocytes, microglia, and SGCs, and their glia-glia and neuronal-glia interactions. After intravenous application, paclitaxel was present in the dorsal root ganglia of the PNS and the CNS of rodents. In vitro, SGC enhanced the expression of pro-inflammatory factors and reduced the expression of neurotrophic factor NT-3 upon exposure to paclitaxel, resulting in predominantly neurotoxic effects. Likewise, paclitaxel induced a switch towards a pro-inflammatory phenotype in microglia, exerting neurotoxicity. In contrast, astrocytes expressed neuroprotective markers and increasingly expressed S100A10 after paclitaxel exposure. Astrocytes, and to a lesser extent SGCs, had regulatory effects on microglia independent of paclitaxel exposure. Data suggest that paclitaxel differentially modulates glia cells regarding their (neuro-) inflammatory and (neuro-) regenerative properties and also affects their interaction. By elucidating those processes, our data contribute to the understanding of the mechanistic pathways of paclitaxel-induced side effects in CNS and PNS.